Submesoscale Coherent Structures on the Continental Shelf - Dauhajre, Daniel P.; McWilliams, James C.; Uchiyama, Yusuke (Journal of physical oceanography, 2017)
Discovery and analysis of submesoscale variability O (0.3–30) km on the continental shelf is made possible by a high-resolution (Δ x = 75 m) Regional Oceanic Modeling System (ROMS) simulation of the Southern California Bight (SCB). This variability is manifest in ubiquitous yet ephemeral coherent structures: fronts, filaments, and vortices. Similar to their open-ocean counterparts, fronts and filaments on the shelf are identified by their strong vertical velocity, surface convergence, cyclonic vorticity, and horizontal density gradient. Life cycles of these features typically last 3–5 days, with the formation dominated by a horizontal advective tendency that increases density and velocity gradients (i.e., frontogenesis). The shape of the coastline and depth of the water column both influence the abundance and spatial orientation of shallow-water fronts and filaments. Closer to shore, fronts and filaments often align themselves parallel to isobaths, and headlands often act as sites of intense vorticity generation through bottom stress. A quasi-steady, approximate momentum balance among rotation, pressure gradient, and vertical mixing—known as turbulent thermal wind (TTW)—often is valid in the strong secondary circulations local to fronts and filaments. However, front and filament circulations subject to strong diurnal variation in surface heating and vertical mixing are inconsistent with steady-state TTW balance. The secondary circulations can induce ephemeral material trapping and substantial vertical heat fluxes on the shelf.